2016
DOI: 10.1016/j.bone.2015.11.016
|View full text |Cite
|
Sign up to set email alerts
|

Physical activity, sedentary behavior, and vitamin D metabolites

Abstract: Physical activity is associated with circulating 25-hydroxyvitamin D (25(OH)D). However, the influence of activity and/or sedentary behavior on the biologically active, seco-steroid hormone 1α,25-dihydroxyvitamin D (1,25(OH)2D) is unknown. We conducted a cross-sectional analysis among ursodeoxycholic acid (UDCA) randomized trial participants (n=876) to evaluate associations between physical activity, sedentary behavior, and circulating vitamin D metabolite concentrations. Continuous vitamin D metabolite measur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
21
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(21 citation statements)
references
References 71 publications
0
21
0
Order By: Relevance
“…The lipophilic vitamin D clusters in adipose tissue and leads to lower levels of circulating vitamin D, and adipose tissue is known to contribute to inflammation in RA. 46 Physical inactivity is common in RA and is associated with inflammatory activity, pain and fatigue, 47 whereas some studies also associate physical inactivity with lower vitamin D levels, including 1,25(OH) 2 D. 48 Low vitamin D levels are common in the elderly 8 and in patients with renal insufficiency. The exclusion of patients over 75 years of age and patients with renal insufficiency could lead to underestimation of the prevalence of vitamin D deficiency in our cohort, compared to the general population, thereby weakening the external validity.…”
Section: Discussionmentioning
confidence: 99%
“…The lipophilic vitamin D clusters in adipose tissue and leads to lower levels of circulating vitamin D, and adipose tissue is known to contribute to inflammation in RA. 46 Physical inactivity is common in RA and is associated with inflammatory activity, pain and fatigue, 47 whereas some studies also associate physical inactivity with lower vitamin D levels, including 1,25(OH) 2 D. 48 Low vitamin D levels are common in the elderly 8 and in patients with renal insufficiency. The exclusion of patients over 75 years of age and patients with renal insufficiency could lead to underestimation of the prevalence of vitamin D deficiency in our cohort, compared to the general population, thereby weakening the external validity.…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, in a study within the UDCA cohort included in the present study, moderate to vigorous physical activity was positively associated with 1,25 (OH) 2 D, with women experiencing the greatest increase (21). Hibler et al (21) suggested that the association between physical activity and vitamin D may be beyond sun exposure and driven (63). The major strengths of the current study include the availability of data from a prospective cohort of >1300 participants with complete data on a wide range of available baseline nutrition, physical activity, and serum vitamin D metabolite data.…”
Section: Discussionmentioning
confidence: 99%
“…Individual adherence score components were also examined for associations with adjusted mean concentrations of 25 (OH)D and 1,25(OH) 2 D. Regression modeling was also used to calculate P-trend. Potential confounders included age, education, race, smoking status, supplement use, season of blood draw, and energy intake (21,22,(38)(39)(40). A covariate was considered to be a confounder if it changed the measure of association by $10% when included in a regression model (41).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…However, 1α,25(OH) 2 D 3 requires activation by the vitamin D metabo1ic pathway (15). Therefore, it is postulated that the aberrant expression of the essential enzymes CYP27A1, CYP27B1, and CYP24A1 may be associated with lung cancer.…”
Section: Introductionmentioning
confidence: 99%